Evaluation of the Feasibility of a Simultaneous Change in the Fractional Composition and the Involvement of Depressant Additives to Obtain Low-Freezing Diesel Fuels - Bogdanov I. A. Ilya Aleksandrovich; Kirgina M. V. Mariya Vladimirovna; Morozova Ya. P. Yana Pavlovna; Altynov A. A. Andrey Andreevich (2022, 2022)
Title screen